2014
DOI: 10.3389/fnagi.2014.00299
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related and tissue-specific effects of tobacco smoking on brain atrophy: assessment in a large longitudinal cohort of healthy elderly

Abstract: We investigated the cross-sectional and longitudinal effects of tobacco smoking on brain atrophy in a large cohort of healthy elderly participants (65–80 years). MRI was used for measuring whole brain (WB), gray matter (GM), white matter (WM), and hippocampus (HIP) volumes at study entry time (baseline, N = 1451), and the annualized rates of variation of these volumes using a 4-year follow-up MRI in a subpart of the cohort (N = 1111). Effects of smoking status (never, former, or current smoker) at study entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 88 publications
4
26
0
Order By: Relevance
“…Our analyses of smoking and RBA indicated that subjects who had smoked on most or all days had a significantly higher RBA compared to subjects who smoked less often. That was consistent with previous studies, which showed significantly greater rate of atrophy in certain regions of the brains of smokers (Durazzo et al, 2012;Duriez et al, 2014;Gallinat et al, 2006). Our data also showed that there was no significant difference of RBA among the subjects who smoked occasionally, only tried once or twice, or abstained from smoking.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our analyses of smoking and RBA indicated that subjects who had smoked on most or all days had a significantly higher RBA compared to subjects who smoked less often. That was consistent with previous studies, which showed significantly greater rate of atrophy in certain regions of the brains of smokers (Durazzo et al, 2012;Duriez et al, 2014;Gallinat et al, 2006). Our data also showed that there was no significant difference of RBA among the subjects who smoked occasionally, only tried once or twice, or abstained from smoking.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with nonsmokers, smokers have significantly smaller grey matter volume and lower grey matter density in the frontal regions, the occipital lobe, and the temporal lobe. Further, smokers have a significantly greater rate of atrophy in regions that show morphological abnormalities in the early stages of Alzheimer's disease (Durazzo et al, 2012;Duriez et al, 2014;Gallinat et al, 2006). It has also been reported that patients with alcohol use disorder show decreased regional grey and white matter volumes in the medial-prefrontal and orbitofrontal cortices.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of earlier [see (1)] and recent (410) studies on smoking-related neurobiological abnormalities employed magnetic resonance (MR)-based morphological measures (i.e., volume and cortical thickness). Overall, the findings indicated smokers demonstrate widespread structural abnormalities that are particularly prominent in anterior frontal lobe subregions (11).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies’ subjects were too young and pack‐years was too small . We only found a few previous studies research the effect of tobacco separately for GM and WM . Algorithm of VBM method also has improved as it was proposed.…”
Section: Introductionmentioning
confidence: 99%